Dog-Assisted Physical Activity Intervention in Children with Autism Spectrum Disorder: A Feasibility and Efficacy Exploratory Study. (4th July 2022) - Abadi, Mahdi Rostami Haji; Hase, Bethany; Dell, Colleen; Johnston, James D.; Kontulainen, Saija
ABSTRACT: Integrating a therapy dog into physical activity sessions may help children with autism spectrum disorder (ASD) to increase physical activity and gain-related health benefits. This exploratory intervention assessed the feasibility of integrating a therapy dog into exercise sessions and its efficacy to improve physical activity outcomes in children with ASD. After two familiarization sessions, we randomly assigned 18 children with ASD (mean age = 10.1, SD = 2.5) into two groups ( n = 9). We used a crossover design and randomized groups to attend a weekly physical activity session with or without a therapy dog for four weeks. Each group had two sessions with the presence of 1–2 therapy dogs and two sessions without a therapy dog. We assessed feasibility by measuring participant attendance to the crossover sessions and retention in the intervention. We measured efficacy by recording light physical activity, moderate to vigorous physical activity (MVPA), number of bone-impacts, and sedentary time using activity monitors (accelerometers) in each session. We compared physical activity outcomes between the crossover sessions with and without a therapy dog using repeated measures MANOVA. Attendance at the sessions was 92% and the retention rate was 90%. Participants had 13% more minutes of light physical activity (mean difference = 3.5 min; 95% CI: 1.2, 5.8 min) and 22% less sedentary minutes (–2.4; –4.3, –0.1) in the sessions with a therapy dog. MVPA and the number of bone-impacts did not differ between the sessions ( p > 0.05). Our results suggest that integrating therapy dogs into physical activity sessions is feasible and it increases light physical activity and decreases sedentary time in children with ASD.